خلق الإنسان في منظور القرآن ومقارنة مع نظرية دارون - Mastura Muhammad Raudin (Universiti Sains Islam Malaysia, 2009)
This research purpose to know in detail about the making of on the creation of human being based on AI-Quran and As-Sunnah view. This is because Al-Quran and As- Sunnah has explained it in detail. Therefore, in this research, the researcher depend on both of this sources beside other references either the Old Testament or the New Testament. There are describing about the existing of human being from the creation Adam a.s, that created from soil until be a complete human. This research also gives a short view about Darwin's theory. He claimed that human is adopted from a monkey. This theory against with Islamic teaching and could menace of human faith. Thus, this research explained, the theory is wrong according to Al-Quran and As-Sunnah. On the other hand, science also proves and accepts about the creation and making of human being in accordance with Al-Quran and As-Sunnah.